A Causal Treatment for X-Linked Hypohidrotic Ectodermal Dysplasia: Long-Term Results of Short-Term Perinatal Ectodysplasin A1 Replacement - Schneider, Holm; Schweikl, Christine; Faschingbauer, Florian; Hadj-Rabia, Smail; Schneider, Pascal (International journal of molecular sciences, 2023)
X-linked hypohidrotic ectodermal dysplasia (XLHED), caused by a genetic deficiency of ectodysplasin A1 (EDA1), is a rare developmental disorder of ectodermal derivatives such as hair, sweat glands, and teeth. The absence of sweat glands and perspiration can evoke life-threatening hyperthermia. As molecular genetic findings are not always conclusive, the concentrations of circulating EDA1 may help to distinguish between total and partial EDA1 deficiencies. We previously treated nine male patients with obvious signs of XLHED with a recombinant EDA1 replacement protein, Fc-EDA, either shortly after birth (n = 3) or by prenatal administration in gestational week 26 and beyond (n = 6). Here, we present the long-term follow-up for up to six years. In patients who had received Fc-EDA after birth, neither sweat glands nor sweating ability were detected at the age of 12–60 months. In contrast, prenatal EDA1 replacement resulted in ample sweat gland development and pilocarpine-inducible sweating in all treated subjects, who also attained more permanent teeth than their untreated affected relatives. Normal perspiration has persisted for six years in the two oldest boys treated repeatedly with Fc-EDA in utero. When they had a sauna, adequate thermoregulation was evidenced. Lower sweat production after single prenatal dosing may indicate a dose–response relationship. The absence of circulating EDA1 in five prenatally treated subjects proved that these children would have been unable to perspire if they had been left untreated. The sixth infant was shown to produce an EDA1 molecule that, albeit interacting with its cognate receptor, cannot activate EDA1 signaling. In conclusion, a causal treatment of XLHED before birth is feasible.